PERANCANGAN JARINGAN LOCAL AREA NETWORK (LAN) DI SEKOLAH SMK 1 KEPAHIANG - Entin Monika; Fitriah Fitriah (CV. Denasya Smart Publisher, 2025)
learning, communication, and data management activities. This study aims to design a LAN network topology that suits the needs and environmental conditions, both at home and in small to medium-scale educational institutions. The methodology used includes hardware requirements analysis, network topology selection, and simulation using software such as Cisco Packet Tracer. The design results show that the use of a star topology for home networks and a combination of star and extended star topologies for schools provide optimal performance in terms of speed, scalability, and ease of maintenance. This design also takes into account aspects of security, cost efficiency, and ease of future development. The development of information technology drives the need for reliable and efficient computer networks, especially in home and school environments. The design of Local Area Networks (LANs) is an important solution in supporting integrated